Activation of AMPK Enhances Neutrophil Chemotaxis and Bacterial Killing - Dae Won Park; Shaoning Jiang; Jean-Marc Tadie; William S. Stigler; Yong Gao; Jessy Deshane; Edward Abraham; Jaroslaw W. Zmijewski (BMC, 2013)
Abstract An inability of neutrophils to eliminate invading microorganisms is frequently associated with severe infection and may contribute to the high mortality rates associated with sepsis. In the present studies, we examined whether metformin and other 5' adenosine monophosphate-activated protein kinase (AMPK) activators affect neutrophil motility, phagocytosis and bacterial killing. We found that activation of AMPK enhanced neutrophil chemotaxis in vitro and in vivo, and also counteracted the inhibition of chemotaxis induced by exposure of neutrophils to lipopolysaccharide (LPS). In contrast, small interfering RNA (siRNA)-mediated knockdown of AMPKα1 or blockade of AMPK activation through treatment of neutrophils with the AMPK inhibitor compound C diminished neutrophil chemotaxis. In addition to their effects on chemotaxis, treatment of neutrophils with metformin or aminoimidazole carboxamide ribonucleotide (AICAR) improved phagocytosis and bacterial killing, including more efficient eradication of bacteria in a mouse model of peritonitis-induced sepsis. Immunocytochemistry showed that, in contrast to LPS, metformin or AICAR induced robust actin polymerization and distinct formation of neutrophil leading edges. Although LPS diminished AMPK phosphorylation, metformin or AICAR was able to partially decrease the effects of LPS/toll-like receptor 4 (TLR4) engagement on downstream signaling events, particularly LPS-induced IκBα degradation. The IκB kinase (IKK) inhibitor PS-1145 diminished IκBα degradation and also prevented LPS-induced inhibition of chemotaxis. These results suggest that AMPK activation with clinically approved agents, such as metformin, may facilitate bacterial eradication in sepsis and other inflammatory conditions associated with inhibition of neutrophil activation and chemotaxis. Online address: https://doi.org/www.molmed.org